Determinantes de los precios de las colegiaturas de las universidades privadas en México 2005-2019 - Miguel Flores Márquez; Alejandrina Salcedo; Leondardo Torre (Banco de México, 2022)
– We estimate a supply and demand model of private college education services in Mexico for the 2005-2019 period, in order to identify the factors that influenced the dynamics of their equilibrium prices. The model is estimated with two- and three-stage least squares using panel data at the state level. The estimates suggest that while the contribution of demand variables to the inflation of such prices has been positive and fairly stable, that of supply variables, even though it has been more fluctuating, it has also been larger than the contribution of the former throughout the entire period. The estimated model is used, in turn, to identify the supply and demand variables that most contributed to the recent acceleration (2016-2018) and subsequent deceleration (2018-2019) of the observed inflation in private college education prices.
Keywords: D12; C20; C23; R10; O54; 330; Tuition Fees; Simultaneous Equations; Panel Data; Regional Analysis; Mexico